2014
DOI: 10.4149/bll_2014_026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the toxic effects of hydroalcoholic extract of Stachys lavandulifolia Vahl on rat’s liver

Abstract: Aims: Stachys lavandulifoliaVahl is a frequently used plant to treat different diseases, but its probable toxic effects have not been reported yet. This study aimed to study the toxicity of the extract on rats' liver. Methods: In this experimental study, 100 rats were designated into 10 groups and injected normal saline or Stachys lavandulifolia Vahl extract at 50, 100, 150, and 200 mg/kg, intraperitoneally for 28 days. Four case groups and one control group were examined for ALT, AST and ALP after one month a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…These results showed that the radical scavenging activity of these plants extracts were higher than BHT. The antioxidant potential and phenolic diversity in many plants have been previously reported [30,31]. In present…”
Section: Cytotoxicity and Antiviral Experimentssupporting
confidence: 56%
“…These results showed that the radical scavenging activity of these plants extracts were higher than BHT. The antioxidant potential and phenolic diversity in many plants have been previously reported [30,31]. In present…”
Section: Cytotoxicity and Antiviral Experimentssupporting
confidence: 56%
“…The toxicity of some of these compounds in in vivo situations might also be due to their pro-oxidant activities (Taghikhani et al 2013). However, in practice the prooxidant activity can be beneficial because by imposing a mild degree of oxidative stress, the levels of biotransformation enzymes and antioxidant defenses might increase, protecting the cells more efficiently (Bahmani et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Heading toward further complications like type 2 diabetes mellitus, heart disease, and stroke (Nasri & Shirzad, 2013). The use of synthetic drugs to control obesity are varied but the usage of these drugs regarding their safety and efficacy are not promising (Taghikhani et al, 2012).…”
Section: A R T I C L E I N F O Abstract Article Historymentioning
confidence: 99%